The Influence of Tax Knowledge, Love of Money, and Tax Discrimination on the Perception of Tax Evasion Ethics - Nurul Adha; Husnul Muttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
As a nation still navigating its path toward broader socioeconomic progress, Indonesia persistently works to elevate the well-being of its citizens through initiatives spanning education, public health, and infrastructure development. This research investigates how individuals’ understanding of taxation, their attitude toward money, and their perceptions of discriminatory tax treatment shape their ethical views regarding tax evasion, specifically among MSME taxpayers in Bengkalis district. A quantitative design was adopted, relying on primary data collected from 100 participants chosen through purposive sampling. Responses were measured using a Likert-based questionnaire, and the analysis wasicarried out usingiSPSS version 25 with multipleilinear regression techniques. The results reveal that greater tax knowledge is associated with a lower tendency to view tax evasion as ethically acceptable. Conversely, a stronger love of money corresponds with a more permissive view of tax-evading behavior. The variable related to perceived tax discrimination, however, did not produce a meaningful effect on ethical judgments about evasion. The Adjusted R² of 28.5% suggests that the examined factors account for just over a quarter of the variance in ethical perceptions, leaving 71.5% attributable to other influences outside the model. Future studies are encouraged to incorporate additional determinants such as perceived fairness, religiosity,quality of tax services, commitment, service quality of tax authorities, and tax penalties.